Theoretical Framework for Business Survival of Tour Agents in Miri - Abdul Rani, Nazatul Shima; Mohd Kassim, S. (The Edge Solutions, 2010)
Miri is a small Malaysian city located at the northern part of Sarawak on Borneo Island. When Miri was declared a Resort City, it raised the question whether travel agencies in Miri have enough capacities and facilities to support the mission of a Resort City in Sarawak. Hence, the purpose of the paper is to propose a theoretical framework for Miri travel agents survival to embrace an e-business model in their operations. The technology acceptance model, e-business and e ticketing will be discussed in detail, in such a way that will ensure the survival of travel agent in Miri, Sarawak, Malaysia.